PENGARUH PEMAHAMAN PAJAK DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN ETIKA MACHIAVELLIAN SEBAGAI PEMEDIASI - Kasun Japar; Estralita Trisnawati (Fakultas Ekonomi Universitas Tarumanagara, 2024)
This study aims to determine whether Machiavellian ethics mediate the influence that exists between understanding tax regulations and taxpayer awareness and taxpayer compliance with MSME actors in Jakarta. Tax compliance decisions can be influenced by the Machiavelli nature of the taxpayer as well as the norms or values ​​of life that are believed by taxpayers. This research is a quantitative analysis research with causality research design with survey method approach. The analytical tool used is Structural Equation Modeling (SEM) for path analysis, with a sample of 190 respondents. The results showed that there was no direct effect of understanding tax regulations and taxpayer awareness on Machiavellian ethics. There is a significant positive direct effect on understanding tax regulations and taxpayer awareness on individual taxpayer compliance with MSME actors, while there is no direct influence on MSME actors' Machiavellian ethics on MSME individual taxpayer compliance. Machiavellian ethics for MSME actors are unable to mediate understanding of tax regulations and taxpayer awareness of individual taxpayer compliance with MSME actors in Jakarta